Hunter Killer - Taylor, Brad 1965- (New York, NY : William Morrow, an imprint of HarperCollins Publishers, 2020)
"Pike Logan tracks highly-trained Russian assassins to Brazil in this blistering, action-packed thriller from New York Times bestselling author and former Special Forces Officer Brad Taylor"--
Booklist
Kirkus Reviews
Publishers Weekly
Library Journal Prepub Alert
Adult
Keywords: Logan, Pike -- Fiction; Terrorism -- Fiction -- Prevention; Spy stories; War stories; Suspense fiction